2007
DOI: 10.1541/ieejsmas.127.258
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Human Activity Using Plant Bioelectric Potential

Abstract: In this paper, we monitored the electromagnetic waves generated by human activity. We investigated a monitoring system that used the bioelectric potential of a plant. Four subjects walked on the spot at a distance of 60 cm from a rubber tree and we measured the variation in the bioelectric potential of the tree produced by the stepping motion. The results confirmed that the electromagnetic waves generated by a person walking on the spot produced a measurable response in the bioelectric potential of a plant. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Many papers have reported that the potential changes with environmental conditions such as illumination, temperature, humidity, gases, watering, and trauma [8][9][10][11]. In addition, several studies have attempted to monitor not only plant activities but also the ambient environment of plants [13], and other studies have attempted to optimize the growing environment and efficiency by using information on the bioelectric potential as a control signal [14]. Therefore, measurement of the bioelectric potential is a promising method of evaluating and monitoring plant activities by physical quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers have reported that the potential changes with environmental conditions such as illumination, temperature, humidity, gases, watering, and trauma [8][9][10][11]. In addition, several studies have attempted to monitor not only plant activities but also the ambient environment of plants [13], and other studies have attempted to optimize the growing environment and efficiency by using information on the bioelectric potential as a control signal [14]. Therefore, measurement of the bioelectric potential is a promising method of evaluating and monitoring plant activities by physical quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Humans are known to elicit a pulsed bioelectric potential response when touching the leaves or stem of a plant . Furthermore, as described above, electrostatic induction results from walking, and the electromagnetic waves caused by human activity have been reported to affect the bioelectric potential . Thus, we focused on behavior in which persons touched or approached a plant.…”
Section: Experimental Systemmentioning
confidence: 99%
“…In addition, plant bioelectric potential is clearly affected by the behavior of humans. In research by Hirobayashi and colleagues , the electromagnetic waves generated by persons when walking are reported to have an effect on the bioelectric potential. Shimbo and colleagues investigated how the bioelectric potential was affected by the behavior of persons entering or leaving a room or watering plants .…”
Section: Introductionmentioning
confidence: 99%
“…Hirobayashi et al found that when a human steps near a plant, there is a correlation between the change of plant bioelectric potential and the step. (2) It is suggested that an electromagnetic wave that is generated by things like a change of a myoelectric potential caused by walking affects an electric signal in a living plant. (1,2) Furthermore, Nomura et al showed that human behavior, such as stepping, walking, and opening doors, can be distinguished on the basis of the difference in the plant bioelectric potential.…”
Section: Introductionmentioning
confidence: 99%
“…(2) It is suggested that an electromagnetic wave that is generated by things like a change of a myoelectric potential caused by walking affects an electric signal in a living plant. (1,2) Furthermore, Nomura et al showed that human behavior, such as stepping, walking, and opening doors, can be distinguished on the basis of the difference in the plant bioelectric potential. (3) However, these studies do not show the relationship between the change in potential and the distance of the plant from the human.…”
Section: Introductionmentioning
confidence: 99%